PENGEMBANGAN APLIKASI MOBILE FORUM DISKUSI MAHASISWA UNIVERSITAS PARAMADINA BERBASIS OBJEK - Putra, Muhammad Daffa Arviano; Darwis, Muhammad; Hendrowati, Retno (ITP Press, 2023)
Forum is a platform for exchanging information and ideas. In the digital era, information is highly valuable, and forums have become an appropriate means to obtain it. As a result, forums are now available in the form of applications. A forum application can provide numerous benefits to its users. In this study, a mobile forum application specifically designed for students of Paramadina University is developed. The presence of this student forum application is expected to enhance collaboration and foster discussions among students, thus enriching their learning experience at Paramadina University. The system development process of the forum application is carried out by applying object-oriented design principles, incorporating the creation of Unified Modeling Language (UML) diagrams. Consequently, the system design follows efficient and standard-compliant structures. The designed system is then implemented into a mobile application using the Dart programming language with Flutter framework. For the backend, the application is developed with Go programming language and MySQL relational database. The forum application developed in this study underwent comprehensive testing to ensure its accuracy and usability, using both blackbox and whitebox methods. The testing results indicated that the forum application functions well. Therefore, the forum application is considered suitable and can be used by students of Paramadina University to collaborate with each other.